The impact of postharvest ultra-violet light irradiation on the thiol content of Sauvignon blanc grapes. (15th January 2019) - Parish-Virtue, Katie; Herbst-Johnstone, Mandy; Bouda, Flo; Fedrizzi, Bruno
Highlights: Ultra-violet (UV) light irradiation can alter wine aroma compound concentrations. After cold settling, no differences in juice thiol precursors between UV treatments. Lower 3-mercaptohexyl acetate wine levels for damaged grapes exposed to UV light. Lower hexan-1-ol wine levels for whole grape bunches exposed to UV light. Abstract: Sauvignon blanc grapes were exposed to an ultra-violet (UV) light source post-hand harvest (whole bunches) or post-machine harvest. The thiol precursors S -3-(hexan-1-ol)-l -cysteine (Cys-3MH) and S -3-(hexan-1-ol)-l -glutathione (GSH-3MH) were quantified in the juices before and after UV treatment. Results showed that irradiation of the grapes with UV light had little to no effect on the thiol precursors. Wines were fermented from the corresponding juices and 18 aroma compounds were quantified. Differences were found between UV treatments of the wines for 3-mercaptohexanol, hexan-1-ol, ethyl butanoate, ethyl hexanoate, ethyl octanoate and phenylethyl alcohol. However, these changes were not significant ( p  < 0.05) for both grape media trialled. Future studies involving larger sample sizes and replicate numbers should be completed in order to ascertain any changes in aroma chemistry as a result of UV light application to grapes postharvest.